Proceedings of the Eleventh ACM International Conference on Multimedia - MULTIMEDIA '03 2003
DOI: 10.1145/957052.957066
|View full text |Cite
|
Sign up to set email alerts
|

Affective content detection using HMMs

Abstract: This paper discusses a new technique for detecting affective events using Hidden Markov Models(HMM). To map low level features of video data to high level emotional events, we perform empirical study on the relationship between emotional events and low-level features. After that, we compute simple low-level features that represent emotional characteristics and construct a token or observation vector by combining low level features. The observation vector sequence is tested to detect emotional events through HM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Kang [4] tried to recognize video affective based on HMMs. Videos were classified into three affective genera named happiness, fear and sad by using low-level visual features.…”
Section: Introductionmentioning
confidence: 99%
“…Kang [4] tried to recognize video affective based on HMMs. Videos were classified into three affective genera named happiness, fear and sad by using low-level visual features.…”
Section: Introductionmentioning
confidence: 99%
“…Most existing methods focus on detecting movie affective content by using low-level features [2,3,4,5]. Kang used HMMs to categorize movie scenes into three types of affective content, joy, fear, and sadness, based on low-level visual features [2]. Xu et al proposed an HMM-based method to detect affective events such as laughter in comedies and terrible sounds in horror movies [3].…”
Section: Introductionmentioning
confidence: 99%
“…These works try to provide an effective and efficient way to manage and access multimedia databases. More recently, researchers have revealed the significance of affective analysis from a personalized media point of view [1][2][3][4]. For example, many users favor a flexible tool to quickly browse the funniest or the most sentimental segments of a movie, as well as the most exciting parts of a sports game video.…”
Section: Introductionmentioning
confidence: 99%
“…fear, sadness and joy). The users' feedbacks [3] were further used to adjust weights to emphasize different features in [2]. In [4], four sound energy events were identified that convey well established meanings through their dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation